The discourses : reflections on history, Sufism, theology, and literature - Yūsī, al-Ḥasan ibn Masʻūd, 1630 or 1631-1691 (Library of Arabic literature., 2019)
"Al-Hasan al-Yusi was arguably the most influential and well-known Moroccan intellectual figure of his generation. In 1084/1685, at the age of roughly fifty-four, and after a long and distinguished career, this Amazigh scholar from the Middle Atlas began writing a collection of short essays on a wide variety of subjects. Completed three years later and gathered together under the title, Discourses on Language and Literature (al-Muhadarat fi l-adab wa-l-lughah), they offer rich insight into the varied intellectual interests of an ambitious and gifted Moroccan scholar, covering subjects as diverse as genealogy, theology, Sufism, history, and social mores. In addition to representing the author's intellectual interests, The Discourses also includes numerous autobiographical anecdotes, which offer valuable insight into the history of Morocco, including the transition from the Saadian to the Alaouite dynasty, which occurred during al-Yusi's lifetime. Translated into English for the first time, The Discourses offers readers access to the intellectual landscape of the early modern Muslim world through an author who speaks openly and frankly about his personal life and his relationships with his country's rulers, scholars, and commoners"--